Analisa Peningkatan Kualitas Pelayanan Kesehatan Di Pusat Pelayanan Kesehatan Paru Kota Cilegon dengan Metode Potential Gain In Customer Values - Leon Hafid EL Rasyid; Ahmad Nalhadi; Supriyadi Supriyadi (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2016)
Improving service quality is one way to improve services so patients can be adequately treated. TB lung disease is one of the diseases that many people experience, so it requires more planned action. This study aims to analyse the attributes that cause patient dissatisfaction and determine improvement strategies to improve service quality. The research was conducted at the Cilegon Lung Health Service Centre using the Importance Performance Analysis and Potential Gain in Customer Value methods. The study used 47 respondents. The results of priority improvements using the IPA method obtained attributes that get priority improvements: the availability of a large parking lot, P2KP equipment facilities, waiting room facilities, reliable and fast examination, treatment and care services, P2KP location, and cleanliness, beauty and comfort of P2KP. At the same time, priority improvements based on Potential Gain in Customer Value are the availability of a large parking lot, P2KP equipment facilities, fast patient admission procedures, waiting room facilities, reliable and fast examination, treatment and care services, P2KP location, ease of patients in submitting complaints, cleanliness, beauty and comfort of P2KP and doctors always on site if needed.